2020
DOI: 10.1002/anie.201916554
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of Cu‐Exchanged Automotive‐Emission NH3‐SCR Catalysts Elucidated with Nanoscale Resolution Using Scanning Transmission X‐ray Microscopy

Abstract: To gain insight into the underlying mechanisms of catalyst durability for the selective catalytic reduction (SCR) of NOx with an ammonia reductant, we employed scanning transmission X‐ray microscopy (STXM) to study Cu‐exchanged zeolites with the CHA and MFI framework structures before and after simulated 135 000‐mile aging. X‐ray absorption near‐edge structure (XANES) measurements were performed at the Al K‐ and Cu L‐edges. The local environment of framework Al, the oxidation state of Cu, and geometric changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…[11][12][13][14] In our previous study of steamed Cu-ZSM-5 zeolites we have observed an unusual NO conversion curve with a 'dip' shape at around 300 °C. 15 A similar drop of NO conversion was reported at ~270 °C with the hydrothermally treated zeolite Cu-SSZ-13 and was simply explained by the accelerated unselective NH3 oxidation promoted by CuxOy clusters/nanoparticles. 16,17 However, the detailed structural reasons for the low NH3-SCR activity have not yet been well understood due to the interference of multiple Cu sites and side reactions.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…[11][12][13][14] In our previous study of steamed Cu-ZSM-5 zeolites we have observed an unusual NO conversion curve with a 'dip' shape at around 300 °C. 15 A similar drop of NO conversion was reported at ~270 °C with the hydrothermally treated zeolite Cu-SSZ-13 and was simply explained by the accelerated unselective NH3 oxidation promoted by CuxOy clusters/nanoparticles. 16,17 However, the detailed structural reasons for the low NH3-SCR activity have not yet been well understood due to the interference of multiple Cu sites and side reactions.…”
Section: Introductionsupporting
confidence: 64%
“…In the 850 °C steamed Cu-ZSM-5, nanoparticles with particle sizes of 2-5 nm were prone to migrate and aggregate on the surface of zeolite particle, which is in agreement with a Scanning Transmission X-ray Microscopy (STXM) study that revealed Cu zoning on the edge of individual catalyst particles in steamed zeolites. 15 The agglomerated Cu species have a less reducible nature than isolated Cu 2+ , as indicated by the higher reduction temperature in the steamed Cu-ZSM-5 observed in H2-Temperature Programmed Reduction (H2-TPR) (Fig. S6).…”
Section: Loss Of Isolated Cu 2+ Sitesmentioning
confidence: 98%
“…The advantage of Cu-zeolite materials over Cu supported on conventional solid carriers can be related to the synergistic effect of acid sites in the zeolite framework and subnanometric Cu species confined in the cavities. Control of the spatial distribution of Cu and Al species is also a key issue on preparation of highly stable Cu-zeolite materials for NH3-SCR reaction 185 .…”
Section: Denox Reactionsmentioning
confidence: 99%
“…It has been proposed that the hydrothermal stability of the Alcontaining zeolite framework is one of the critical factors for the NH 3 -SCR. [24] In this regard, we previously reported that the addition of rare-earth ions, especially Y, can stabilize the framework Al of a CHA matrix. [5a] In the present study, the effects of different rare-earth ions on activity and hydrothermal ChemCatChem stability of Cu-AEI were also investigated.…”
Section: Hydrothermal Stabilitymentioning
confidence: 99%